2002
DOI: 10.1021/om0200196
|View full text |Cite
|
Sign up to set email alerts
|

Hydrosilylation with Bis(alkynyl)(1,5-cyclooctadiene)platinum Catalysts:  A Density Functional Study of the Initial Activation

Abstract: At elevated temperatures bis(alkynyl)(1,5-cyclooctadiene)platinum complexes catalyze the cross-linking of polyorganosiloxanes containing Si−H and vinyl groups. Density functional calculations with medium-size basis sets and effective core potentials are reported for reactions that may activate these precatalysts for hydrosilylation. For a model system consisting of the bis(ethynyl) complex, trimethylsilane, and ethylene, the computations provide two plausible pathways for gaining access to the Chalk−Harrod cyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 41 publications
0
30
0
Order By: Relevance
“…It is known that palladium‐catalyzed reactions of hydrosilanes are involved in a number of important synthetic methodologies, and the oxidative addition of palladium(0) species to the Si−H bond is considered to be an important fundamental step. Similar to palladium‐ or platinum‐catalyzed hydrosilylation of alkynes and alkenes with hydrosilane, hydrosilane is initially coordinated to the palladium(0) catalyst to form a characteristic Pd 0 ‐η 2 ‐hydrosilane complex ( Cplx1 ) with a stabilization energy of 8.9 kcal mol −1 . Then, oxidative addition of palladium(0) complex O to the Si−H bond of 2 a proceeds smoothly with a low free energy barrier of 2.5 kcal mol −1 via TS OA , leading to a R 3 Si−Pd II −H intermediate ( A ), in which the hydrogen atom is cis to the silyl group.…”
Section: Resultsmentioning
confidence: 99%
“…It is known that palladium‐catalyzed reactions of hydrosilanes are involved in a number of important synthetic methodologies, and the oxidative addition of palladium(0) species to the Si−H bond is considered to be an important fundamental step. Similar to palladium‐ or platinum‐catalyzed hydrosilylation of alkynes and alkenes with hydrosilane, hydrosilane is initially coordinated to the palladium(0) catalyst to form a characteristic Pd 0 ‐η 2 ‐hydrosilane complex ( Cplx1 ) with a stabilization energy of 8.9 kcal mol −1 . Then, oxidative addition of palladium(0) complex O to the Si−H bond of 2 a proceeds smoothly with a low free energy barrier of 2.5 kcal mol −1 via TS OA , leading to a R 3 Si−Pd II −H intermediate ( A ), in which the hydrogen atom is cis to the silyl group.…”
Section: Resultsmentioning
confidence: 99%
“…Quantumchemical calculations using DFT methods studying the activation steps of these complexes came to the conclusion that the activation of the pre-catalyst (COD)Pt(C CR) 2 is initiated by oxidative addition of Si-H. The activation energy and activation temperature depend on the substituents R in the alkynyl groups [172].…”
Section: "Dormant" Platinum Complexes With Inhibiting Ligandsmentioning
confidence: 99%
“…A more recent publication39 by Bartlett et al reported the results of a computational study of reductive elimination reactions from platinum complexes and provides references to other recent work in this specific field. Another example of the application of computational tools to the study of these reactions can be found in the article by Jagadeesh et al,40 which examines the initial platinum catalyst activation in hydrosilation reactions.…”
Section: The Chemistry Of Platinummentioning
confidence: 99%